Market chain analysis of fruits for Gomma Woreda, Jimma Zone, Oromia National Regional State - Tadesse, A. (Haramaya University, 2011)
In support of stimulating growth, economic development, food security and alleviating poverty, the analysis of the marketing performance of fruits plays an important role in an ongoing or future fruit development plan. In spite of the policy options provided by the Ethiopian government, there is very little empirical evidence on the fruit marketing system to design appropriate policies for its improvement of fruit marketing in the study area. Therefore, this study was aimed at analyzing the market chain of fruit for Gomma woreda, Jimma Zone of Oromia National Regional State with the specific objectives of identifying the major fruit marketing channels; quantifying the costs and margins for key fruit marketing channels and identifying factors influencing fruit marketable supply in the study area. In order to attain these objectives the study made use of primary and secondary data. The data were generated by individual interview schedules and focus group discussions using pretested semi structured questionnaires and checklists respectively. This was supplemented by secondary data collected from different published and unpublished sources. Structure, Conduct and Performance (SCP) approach was used to evaluate avocado and mango market and Multiple Linear Regression Model was fitted to identify factors influencing the marketable supply of avocado and mango in the study area. Structure of the market indicates that licensing and years of avocado and mango trade experience did not hinder entry into avocado and mango trade, but capital, education and market information were barriers to enter into the trade. Analysis of marketing costs and margins revealed that processors (juice house) received the highest (88.73%) marketing margin and producers received the least (11.27%) marketing margins in avocado and mango trade business. Based on regression model, the study has identified the main determinants of avocado and mango quantity supply. Quantity of avocado produced, experience, education and price of avocado in the previous year are factors that significantly affect quantity of avocado supplied to the market positively at 1%, 5%, and at 10% level, respectively while lack of market access affects the supply negatively at 10% level. Similarly quantity of mango produced, education and extension contact are factors that significantly affect quantity of mango supplied to the market positively. Therefore one of the most important variables influencing the market supply of avocado and mango is avocado and mango quantity produced due to this, extension work should focus on encouraging farmers to participate in avocado and mango production. This particularly includes, capacity building, technological applications, improved extension and plant breeding activities, there is also a need to increase new varieties that are disease resistant and disseminate these technologies to potential areas. The findings suggests that, effective market information service has to be established to provide accurate and timely market information to farmers and traders on current supply of avocado and mango output, demand and prices at national and regional levels. Infrastructural development is also a key to support the sub-sector. In this arena, emphasis should be given to improved storage and transportation system, offering credit and other services to improve effective production and marketing of avocado and mango.